Equivalent stator slot model of temperature field for high torque-density permanent magnet synchronous in-wheel motors accounting for winding type. Issue 2 (7th March 2016) - Liang, Peixin; Pei, Yulong; Chai, Feng; Cheng, Shukang
Abstract : Purpose: – For high torque-density permanent magnet synchronous in-wheel motor, service life and electromagnetic performance are related directly to winding temperature. The purpose of this paper is to investigate the equivalent stator slot model to calculate the temperature of winding accurately. Design/methodology/approach: – This paper analyzes the the law of heat flux transfer in slot, which points the main influence factors of equivalent stator slot model. Thermal network model is used to investigate the drawbacks of conventional equivalent model. Based on the law of heat transfer in stator slot, a new layered winding model is put forward. According to winding type and property of impregnations, detailed method and equivalent principle of the new model are presented. The accuracy of this new method has been verified experimentally. Findings: – An accurate equivalent stator slot model should be built according to the low of heat transfer. According to theory analysis, the drawbacks of conventional equivalent stator slot model are pointed: it cannot reflect the temperature gradient of winding; the maximum and the average temperature of winding are much higher than actual value. For the new layered model, equivalent principle is related to winding type and property of impregnations, which makes the new model widely used. Originality/value: – This paper presents a new layered model, and shows detailed method, which is more meaningful for designers. The new layered model takes winding type and property of impregnations into account, which makes the new model widely used. It is verified experimentally that layered model is applicable to not only steady-state temperature field but also transient temperature field.